Pengaruh Pemasaran Online dan Modal Kerja terhadap Pendapatan UMKM (Studi Kasus Umkm Olahan Hasil Pertanian di Kota Tangerang) - Violina, Dhea; Sumantri, Ari Tresna; Mirajiani, Mirajiani; Setiawan, Johan (JURNAL AGRIBISNIS TERPADU, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are business entities carried out by groups, individuals, households, up to small business entities that meet the standards as micro businesses. The purpose of this study is to analyze the effect of online marketing and working capital partially and simultaneously on the income of MSMEs Processed Agricultural Products in Tangerang City. This study uses a quantitative method with primary and secondary data sources. The population in the study refers to agricultural product processing business actors in Tangerang City which are fostered by the Tangerang City Industry, Trade, Cooperatives and MSMEs Service. The sampling technique uses the Probability Sampling technique with the Simple Random Sampling method. The determination of the sample is calculated using the Slovin formula which obtained the results of 95 respondents. The data analysis technique in this study uses the multiple linear regression analysis method. Multiple linear analysis obtained that Online Marketing (X1) was 0.326 with a t-count value of 2.788 and t-table (Sig 0.05) and Working Capital (X2) was 0.281 with a t-count value of 2.454 and t-table (Sig 0.05). The results of the determination coefficient analysis (R²) were 0.131, meaning that 13.1% of the Online Marketing (X1) and Working Capital (X2) variables had a significant effect on the UMKM Income variable (Y), while the other 86.9% could be explained by other variables outside of this study.